Designing Nanostructured Organic-Based Material by Combining Plasma Polymerization and the Wrinkling Approach - Vinx, Nathan; Tromont, David; Chauvin, Adrien; Leclère, Philippe; Snyders, Rony; Thiry, Damien (Langmuir, 2023)
In this work, an innovative and versatile strategy for the fabrication of nanostructured organic thin films is established based on the wrinkling phenomenon taking place in a bilayer system constituted by a liquid plasma polymer film (PPF) and a top Al coating. By means of morphological characterization (i.e., atomic force microscopy and scanning electron microscopy), it has been demonstrated that the wrinkle dimensions (i.e., wavelength and amplitude) evolve as a function of the PPF thickness according to models established for conventional polymers. The wrinkled surfaces exhibit great stability over time as their dimension did not vary after 100 days of aging, resulting from a pinning phenomenon between the Al layer and the Si substrate, hence freezing the morphology. In a second step, the wrinkled surfaces have been employed as templates for the deposition of an additional PPF third layer, giving rise to the formation of a nanostructured organic-based surface. The chemical composition of the material can be tuned through an appropriate choice of precursor (i.e., allyl alcohol or propanethiol).